Experimental Investigation of Dynamic Behavior of Shallow Foundation Resting on the Reinforced Sand with Embedded Pipes - Boushehrian, Alireza Hajiani; Afzali, Amid (International Journal of Geography and Geology, 2016)
One of the major concerns is to do with the foundations, such as compressors, railroads, roads and so forth, which are under the influence of the static and dynamic loads. These foundations which have been affected by the traffic loads are regarded as uniform and differential settlements. Sometimes a number of pipes are laid under these foundations, thereby influencing the related settlements. In this study, it has been shown that an increase in the dynamic load when both the initial static load and the pipe depth are constant leads to an increase in the settlement. As compared to the ordinary condition, the amount of settlement is greater. Also, it was revealed that the amount of soil settlement is reduced by 54%, as compared with the unreinforced soil, considering that the initial static load and the pipe depth are constant, and that the dynamic load has been applied, and that the grid-anchor system has been used. This research has focused mainly on introducing an appropriate and unified strategy to improve soil behavior using the reinforcements, which reduce the soil settlement in these shallow foundations. In addition, this paper presents the equations for both reinforced and unreinforced soil under dynamic loading to prevent such complicated calculation involved in deformation analysis. According to these equations, calculation of the permanent settlement for each foundation with a given size on the grid-anchor reinforced sand with and without embedded pipe is feasible.